A WGS84-AHD Profile over the Darling Fault: Western Australia - Friedlieb, Owen; Featherstone, Will; Dentith, M. (Institution of Surveyors, Australia, 1997)
The Darling Fault near Perth in Western Australia causes a steep geoid gradient of approximately 100mm/km. Existing gravimetric geoid models cannot currently recover this rapidly varying geoid undulation with sufficient accuracy so as to allow the accurate determination of Australian Height Datum (AHD) heights using the Global Positioning System (GPS). As such, the geometrical approach to determine the separation between the AHD and World Geodetic System 1984 (WGS84) ellipsoid is expected to offer improved GPS height determination in this region. A network of 45 carrier-phase GPS baselines, made at 14 first-order AHD benchmarks at ~3km intervals along a 30km profile across the Darling Fault near Perth, was observed in order to test this hypothesis. Several GPS network adjustment strategies were implemented which constrained existing height information in different ways. Due to the poor knowledge of the position of the geoid in this region, the most precise network adjustment used only one fixed ellipsoidal height and all other known stations were held fixed in latitude and longitude only. When the geometrical approach was compared with the results of existing gravimetric geoid solutions, it offers a superior means of determining heights from GPS. However, the geometrical method only satisfies third-order specifications in 5 of the 12 cases tested in this region of the Darling Fault.